3D Human Motion Editing and Synthesis: A Survey. (19th June 2014) - Wang, Xin; Chen, Qiudi; Wang, Wanliang
Abstract : The ways to compute the kinematics and dynamic quantities of human bodies in motion have been studied in many biomedical papers. This paper presents a comprehensive survey of 3D human motion editing and synthesis techniques. Firstly, four types of methods for 3D human motion synthesis are introduced and compared. Secondly, motion capture data representation, motion editing, and motion synthesis are reviewed successively. Finally, future research directions are suggested.